How to minimise the negative impact of extended travel on performance - Meir, R.; Hill, R. (2000)
This review will summarize how air travel affects you and what the athlete and coach can do to better prepare for traveling before, during, and after their arrival to minimize the negative aspects and maximize performance. What Is Jet Lag? Are There Individual Differences? Why Does Air Travel Affect You? What Is The Impact On Performance? What Are Some Of The Strategies Used To Minimise Jet Lag? Conclusions: What Do You Need To Know To Minimize The Negative Affects Of Jet Lag?